I-GEL versus LMA classic: Comparison of two supraglottic airway devices in short surgical procedures - Biswas, Tinamoni; Nath , Manisankar; Nandi, Amitayu; Haldar, Purba; Mousumi Neogi (Asian Journal of Medical Sciences, 2022)
Background: Supraglottic airway devices are more efficient than endotracheal intubation in management of difficult airway and hemodynamic response. Aims and Objectives: This study was undertaken for to compare laryngeal mask airway (LMA) Classic and I-Gel in terms of ease of insertion, insertion attempts, time taken for insertion, hemodynamic change, and adverse events after administering muscle relaxants for airway management in short surgical procedures. Materials and Methods: A total of 120 patients of American Society of Anaesthesiologist 1 and II, aged between 18 and 50 years with Malampatti score 1 and II posted for elective short surgical cases were randomly allotted into two groups (n=60 in each), Group A for LMA Classic and Group B for I-gel. Patients were pre oxygenated with 100% O2 and pre-medicated. After induction and proper muscle relaxation, LMA Classic or I-GEL was inserted. The time and number of insertion attempts were assessed. Heart rate, Blood pressure, SpO2 recorded at the time of insertion, 1, 3, 5, and 10 min following insertion. The recorded results were analyzed statistically. Results: The mean insertion time of Group A was 34.80±3.193 and Group B was 21.72±1.975. P<0.001 and in Group B all patients were successfully intubated at first attempt whereas in Group B 23.33% patients required second attempts. Hemodynamic changes were also less with Group B. Conclusion: I-Gel has better hemodynamic stability. Ease of Insertion, insertion attempts and time taken for insertion are more convenient for I-Gel than LMA Classic after administering muscle relaxants.